Under-Graduate Rural Students’ Perception on Soft-Skills Training Workshops to Enhance Employability Opportunities - S , Dr Bhavani (International Journal of Psychosocial Rehabilitation, 2020)
This study focuses on the effectiveness of training workshops on soft-skills to strengthen required skills for the workplace among rural Under-Graduate students of Virudhunagar and Tirunelveli districts in Tamil Nadu. Most students face the challenge of entering reputed job positions due to the lack of effective communication skills in the workplace. This research is based on the responses of college students from two districts in Tamil Nadu who underwent an intensive training workshop to hone their language skills with specific focus on developing soft skills. While most of the students are strong in their hard-skills, they do not have sufficient training in soft-skills and hence the challenge becomes an impediment in seeking job opportunities. The method used is training workshop and responses from the participants were collected using a Likert scale response sheet to determine the effect of the workshop. The results collected are statistically presented which records the students’ perception on the effectiveness of the workshop.